Arguing over Transportation Sales Taxes: An Analysis of Equity Debates in Transportation Ballot Measures. Issue 2 (March 2020) - Lederman, Jaimee; Brown, Anne; Taylor, Brian D.; Wachs, Martin
What's a fair way to pay for urban transportation? Local option sales taxes (LOSTs) for transportation are an increasingly common mechanism for locally financing transportation in the context of declining federal and state funding. LOSTs are typically regressive, raising equity concerns. But their fairness also depends on who benefits from them, based on which projects are funded, where projects are located, and when investments occur. We examine how perceptions of these four dimensions of equity (income, geographic, temporal, and modal) are represented and debated in the ballot arguments for 38 LOST elections in California. We find that measure supporters use subtle language to imply that proposed expenditure plans achieve equity on all dimensions, promising "something for everyone." Measure opponents, by contrast, typically attack specific perceived inequities in proposed expenditure plans. We find that tradeoffs among types of equity debated in ballot arguments frame winners and losers across multiple equity dimensions.